The impact of top management support, perceived justice, supplier management, and sustainable supply chain management on moderating the role of supply chain agility - Men, Feng; Yaqub, Rana Muhammad Shahid; Yan, Rui; Irfan, Muhammad; Haider, Ali (Frontiers in Environmental Science, 2023)
Sustainable supply chain management (SSCM) is a new area of interest to scientists and industrial practitioners to maintain productivity, reduce costs, and enhance agility. Sustainable supply chain management is especially important to protect the environment and reduce the pollution of heavy industries. It considers the environment the main stakeholder in minimizing the carbon footprints during production, low emissions of dangerous gases, and industrial pollution. Keeping in view the above purposes, this study aims to find the relationship between top management support, perceived justice, supplier management, and sustainable supply chain management with the moderating role of supply chain agility. It was a quantitative study conducted in the vast textile sector in Pakistan. We have collected data through a questionnaire survey. The study found that top management support, perceived justice, and supplier management are positively and significantly associated with sustainable supply chain management. While the moderating effect of supply chain agility between the independent variables and sustainable supply chain management has been insignificant. The study findings have practical implications for production managers and top management to enhance their role in environmental well-being. By developing rules at the organizational and governmental levels that consider the role of top management, perceived justice, and improved supplier management, the sustainability of the supply chain can be improved. The study offers academics in the supply chain literature a practical prescription. The thorough investigation adds to the body of knowledge about the top sustainable supply chain management pillars' validity.